Research from the International Network for Bamboo and Rattan (INBAR) enabled the development of the 2019-2030 Ethiopian Bamboo Development Strategy and Action Plan - CGIAR Research Program on Forests, Trees and Agroforestry (2020)
Developing a National Bamboo Strategy and Action Plan, approved and ratified by the Ethiopian government, is a key step towards supporting a self-sufficient and thriving bamboo industry.